Carbon Nano‐Onion and Zinc Oxide Composites as an Electron Transport Layer in Inverted Organic Solar Cells. Issue 2 (5th December 2019) - Bobrowska, Diana M.; Castro, Edison; Echegoyen, Luis; Plonska‐Brzezinska, Marta E.
Abstract: We report a facile chemical method to synthesize hybrid nanocomposites containing carbon nano‐onions (CNOs) and zinc oxide or hydroxide. The structure, surface morphology, optical properties and surface area of the CNOs were characterized by X‐ray diffraction, scanning electron microscopy with energy dispersive spectroscopy, transmission electron microscopy, thermogravimetric analysis, infrared and Raman spectroscopies, and adsorption/desorption N2 techniques. For the first time, we demonstrate the fabrication of bulk heterojunction organic solar cell devices utilizing hybrid nanocomposites containing CNOs and ZnO as the electron transport layer. This configuration showed good photovoltaic performance with maximum external quantum efficiencies of 16.5 and 48.9% and power conversion efficiencies of 0.42 and 1.49% for the pristine ZnO and CNO/ZnO (mCNO  : mZnO =1 : 4) layers, respectively. Abstract : Add onions : A facile chemical method to synthesize hybrid nanocomposites containing carbon nano‐onions and zinc oxide or hydroxide were reported. The fabrication of bulk heterojunction organic solar cell devices utilizing hybrid nanocomposites as the electron transport layer was demonstrated.